Laboratory Diagnosis of Lupus Anticoagulants for Patients on Oral Anticoagulant Treatment - Tripodi, Armando; Chantarangkul, Veena; Clerici, Marigrazia; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2002)
The detection of lupus anticoagulant (LA) in plasmas from patients on oral anticoagulants is problematic because of their prolonged clotting times. Mixing of patients and normal plasmas prior to testing for LA is employed to overcome this problem. We investigated the diagnostic efficacy of silica clotting time (SCT) and dilute Russell viper venom test (dRVVT) performed at low and high phospholipid concentrations, to diagnose LA in patients on oral anticoagulants, in comparison with Staclot® LA (Stago) performed with and without hexagonal phospholipids and normal plasma. Case materials were 114 filtered plasmas from patients on oral anticoagulants with (n = 62) and without (n = 52) the antiphospholipid syndrome. Plasmas were considered LA-positive when Staclot® LA (taken as the “gold standard”) was diagnostic for LA. Forty-four plasmas were positive with Staclot® LA. Forty and 39 of these were also positive with SCT and dRVVT (sensitivity relative to Staclot® LA was 91% and 89%, respectively). Seventy plasmas were negative with Staclot® LA. Three of these were positive with both SCT and dRVVT (specificity relative to Staclot® LA was 96%). Kappa values for measure of agreement were 0.87 and 0.85 (p <0.001), respectively. In conclusion, SCT and dRVVT performed at low and high phospholipid concentrations without normal plasma can be considered as reliable as Staclot® LA peformed with hexagonal phospholipids and normal plasma to diagnose LA in patients on oral anticoagulants. Advantages of SCT and dRVVT over Staclot® LA are easy automation, no need for normal plasma and relatively low cost.
Keywords: Lupus anticoagulant; oral anticoagulation; thrombosis